Front side illuminated dye-sensitized solar cells using anodic TiO2 mesoporous layers grown on FTO-glass - Lee, Kiyoung; Kim, Dam-Hee; Berger, Stefan; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2012)
In the present work, we investigate the performance of anodic, self-organized TiO2 mesoporous structures (TMSs) in dye-sensitized solar cells (DSSCs) under front-side illumination conditions. In order to fabricate structures usable in a front-side (FS) configuration, TMSs were formed on FTO glass by a full anodic conversion of evaporated Ti films on the glass substrate in a glycerol/K2HPO4 electrolyte at 180 °C. The resulting mesoporous layers can be assembled to FS dye sensitized solar cells which show a thickness of only 3 extgreekmm and a remarkable efficiency of 4.34%. This is significantly higher than, for example, anodic TiO2 nanotubes of the same length even after efficiency enhancing TiCl4 treatments (3.01%). The best efficiency value for TMS-based DSSCs that we currently reached is for a 7 extgreekmm thick TMS layer, this is ≈6.82% which is highly promising for further improvements.
EAM Import::2019-03-14

TiO2-WO3 Composite Nanotubes by Alloy Anodization: Growth and Enhanced Electrochromic Properties - Nah, Yoon-Chae; Ghicov, Andrei; Kim, Dam-Hee; Berger, Stefan; Schmuki, Patrik (Journal of the American Chemical Society, 2008)
The present work demonstrates that uniform and highly ordered arrays of TiO_2-WO_3 nanotubes can be grown by anodization of Ti alloys in an ethylene glycol/fluoride based electrolyte under selected electrochemical conditions. These aligned mixed oxide nanotube structures are highly suitable for enhanced electrochromic reactions; in particular we show that already small amounts of WO_3 (such as 0.2 at%) present in the tube oxide drastically improve the electrochromic properties (contrast, onset potential, cycling stability) of nanotube layer based devices.
EAM Import::2019-03-13

TiO2 Nano Test Tubes as a Self-Cleaning Platform for High-Sensitivity Immunoassays - Song, Yanyan; Schmidt-Stein, Felix; Berger, Stefan; Schmuki, Patrik (Small, 2010)
High-aspect-ratio TiO2 nanotube (TiNT) layers can be used as low-cost, low-volume arrays for fluorescence immunosensing. High sensitivity for antibodies at a concentration of 0.01 pg mL-1 is provided by the high observation length (L) of the nanotubes. The photocatalytic properties of TiO2 make the TiNT arrays reusable after a short UV treatment.
EAM Import::2019-03-13